Where Is God in the Megilloth?: A Dialogue on the Ambiguity of Divine Presence and Absence - Melton, Brittany N. (Tyndale bulletin, 2018)
By Brittany N. Melton. A dissertation exploring the ambiguity of divine presence and absence in the Megilloth, arguing that a straightforward presence/absence bifurcation is misleading.